Wearable neuroimaging: Combining and contrasting magnetoencephalography and electroencephalography - Boto, Elena; Seedat, Zelekha A.; Holmes, Niall; Leggett, James; Hill, Ryan M.; Roberts, Gillian; Shah, Vishal; Fromhold, T. Mark; Mullinger, Karen J.; Tierney, Tim M.; Barnes, Gareth R.; Bowtell, Richard; et al. (NeuroImage (Orlando, Fla.), 2019)
One of the most severe limitations of functional neuroimaging techniques, such as magnetoencephalography (MEG), is that participants must maintain a fixed head position during data acquisition. This imposes restrictions on the characteristics of the experimental cohorts that can be scanned and the experimental questions that can be addressed. For these reasons, the use of ‘wearable’ neuroimaging, in which participants can move freely during scanning, is attractive. The most successful example of wearable neuroimaging is electroencephalography (EEG), which employs lightweight and flexible instrumentation that makes it useable in almost any experimental setting. However, EEG has major technical limitations compared to MEG, and therefore the development of wearable MEG, or hybrid MEG/EEG systems, is a compelling prospect. In this paper, we combine and compare EEG and MEG measurements, the latter made using a new generation of optically-pumped magnetometers (OPMs). We show that these new second generation commercial OPMs, can be mounted on the scalp in an ‘EEG-like’ cap, enabling the acquisition of high fidelity electrophysiological measurements. We show that these sensors can be used in conjunction with conventional EEG electrodes, offering the potential for the development of hybrid MEG/EEG systems. We compare concurrently measured signals, showing that, whilst both modalities offer high quality data in stationary subjects, OPM-MEG measurements are less sensitive to artefacts produced when subjects move. Finally, we show using simulations that OPM-MEG offers a fundamentally better spatial specificity than EEG. The demonstrated technology holds the potential to revolutionise the utility of functional brain imaging, exploiting the flexibility of wearable systems to facilitate hitherto impractical experimental paradigms. •Introduction of second generation, smaller, lighter, and highly sensitive OPMs for MEG.•First demonstration of simultaneous EEG and OPM-MEG measurements.•OPM-MEG shown to be less sensitive to artefacts when subjects are allowed to move.•OPM-MEG shown to exhibit fundamentally better theoretical limit on spatial resolution.